General Pathophysiology : Manual for the students of the 2nd course field of study 22 «Health Care» specialty 221 «Dentistry» educational qualification «Master of Dentistry» professional qualification «Dentist» - Melnikova, O. V.; Grekova, T. A.; Ivanenko, T. V.; Kadzharyan, Y. V.; Danukalo, M. V.; Isachenko, M. I.; Мельнікова, Ольга Валеріївна; Грекова, Тетяна Анатоліївна; Іваненко, Тарас Васильович; Каджарян, Єлизавета Віталіївна; Данукало, Максим Вікторович; Ісаченко, Марія Ігорівна (Запорізький державний медико-фармацевтичний університет, 2023)
The aim of the manual is to provide students with an introduction to clinical medicine through the study of diseases as manifestations of pathophysiology. This manual is an introduction to the concepts of health and disease in human populations and the principles and mechanisms of the disease processes. The various components and interactions of the body’s defence system and the relationship of environmental factors to the disease process are considered. The morphology, pathogenesis and clinical course of diseases are presented in detail. There are one two hour lecture per two weeks and two hour practical classes per two week. You are expected to attend all lectures and practical classes as they are a core component to developing your skills and knowledge. The Manual corresponds to the Work Program in pathophysiology for students of mrdical faculties. This subject introduces the student to the study of pathophysiology. The course is divided into two parts. Part one covers basic concepts of pathophysiology. Part two covers pathophysiology of organs and systems. All topics include discussion on dysfunction from cellular to systemic level.